Larval morphology predicts geographical dispersal range of Eastern Pacific eels. (27th June 2019) - Dale, Katherine E; Tinker, M Timothy; Mehta, Rita S
Abstract: The geographical range of many marine species is strongly influenced by the dispersal potential of propagules such as eggs and larvae. Here, we investigate morphological diversity and the effect of body shape on geographical range of leptocephali, the unique, laterally compressed larvae of eels (order Anguilliformes). We used phylogenetically informed analyses to examine the morphological variation of larvae for 17 Eastern Pacific eel species from three adult habitats. We also investigated whether morphological traits of leptocephali could predict larval latitudinal range, hypothesizing that body shape may influence passive dispersal via currents. We found that no two species shared the same multivariate growth trajectories, with the size and scaling of pectoral fin length and snout-to-anus length being particularly variable. Larvae with longer relative predorsal and snout-to-anus lengths at median sizes exhibited wider larval geographical ranges. Body aspect ratio and maximum body length at metamorphosis, two traits we hypothesized to be important for passive transport, were not significant predictors of maximal larval range. We discovered an increase in phylogenetic signal over larval development as eels approach metamorphosis, potentially due to similar selective pressures between related species (such as juvenile habitat or adult morphology). Lastly, we conclude that larval body shape is probably influenced by adult habitat and adult morphology.